International journal of wavelets, multiresolution and information processing. (New Jersey : World Scientific, 2003)
Access available from 2003-
Also issued via World Wide Web
Keywords: Image processing -- Digital techniques -- Periodicals; Wavelets (Mathematics) -- Periodicals